Aerodynamics investigation of delta wing at low Reynold’s number - Hamizi, Ilya Bashiera; Khan, Sher Afghan (Penerbit Akademia Baru, 2019)
A numerical simulation has been carried out to investigate the aerodynamics of an oscillating delta wing and to evaluate the flow structure over the leading edge at different low Reynolds numbers. The numerical results of the coefficient of lift (CL) vs angle of attack are validated with the experimental results from the previous study. Effects of Reynolds number and angle of attack is investigated for the wing lift coefficient and the aerodynamic efficiency. Pressure contour and turbulence kinetic energy are also observed in each case. Vortex formation from each case is noted from pressure contour and lift coefficient. The stall condition is also observed. Considering the three Reynolds number at max CL, which is an angle of attack of 40 degrees, the CL only increased by 0.01, which is not a very significant increase. But L/D ratio has increased significantly for Reynolds number in the range from 8x104 to 1.5x105 and from Re 1.5x105 to 2.68x105. Whereas for each Reynolds number, the lift coefficient CL seems to attain the highest value of 0.4 at the angle of incidence between 10 degrees and -10 degrees to -20 degrees.